Abordagem integrada para avaliação das áreas de aterros comuns em Pereiro/CE - Aquino, Yara Caroline de (Universidade Federal Rural do Semi-Árido, 2018)
The improper disposal of these in common landfills causes damage to public health and edaphic, water and atmospheric contamination. Therefore, the study objetive was make an integrated approach for evaluation of dumping areas, in order to demonstrate the anthropic pressure imposed by the systems in use and deactivated. For this, the research had exploratory character with the realization of in loco visits. With the help of the GPS Garmin 78s receiver equipment was georeferenced the location of the analyzed area made photographic records of the scenarios in question. For the characterization of common landfills interviews were conducted with public waste collectors and local waste pickers. Besides that, were used the technological tools for obtaining satellite images and spatialization of field data, associated with the delimitation of the microbasin of the Adauto Bezerra spring, with the purpose of determining the water susceptibility. Based on the consulted bibliography and with data access of annual precipitation, besides the accomplishment of the gravimetric composition analysis, it was also possible to estimate the average leachate flow rate of the current landfill system of Pereiro/CE. The diagnosis of the ten common landfills was due to the collective memory. Therefore, parameters such as structural, administrative and location, among others, were used in order to know the space-time distribution and the anthropic pressure imposed by them. The general overview allowed to classify them as critical risk degree, with great potential to cause negative environmental impact. The gravimetric composition of the waste from the common landfill of Lages farm demonstrated a higher percentage of organic solid waste (34%), which associated with the leachate flow estimate (0,1098 L/s) and the proximity to the drainage network shows the great potential that it has to cause contamination of the Adauto Bezerra spring.
Artigo Acadêmico
Keywords: Lixão; Resíduos Sólidos; Gravimetria; Lixiviado; Bacia Hidrográfica; ENGENHARIAS::ENGENHARIA SANITARIA